INPLEMENTASI CONTEXTUAL TEACHING AND LEARNING DALAM KTSP MATA PELAJARAN BIOLOGI - Jailani, Jailani (UNIVERSITAS SERAMBI MEKKAH, 2012)
Abstract: The competence based curriculum allows the regions or schools to develop their own syllabi that refer to the basic competence set by the curriculum center. Competence is to des cribe a person as competent in area of work if they have the knowledge, skill, and attitudes to be able to function at some minimum acceptable level. The competence based curriculum (CBC) must be followed up by developing its syllabi. Thereby the syllabi will be more relevant the condition and the interest of the regeonal stakeholders. The teaching method should be contextual. This article, concerns a critical analysis of how the learning experience and the teaching materials of biology subject are designed based on Contextual Teaching and Learning (CTL). The student must have contacts with the real world. Education quality will improve along with learning process improvement.